2017
DOI: 10.2967/jnumed.117.192476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-PSMA-11 PET on Management in Patients with Biochemically Recurrent Prostate Cancer

Abstract: The purpose of this prospective study was to estimate the effect of Ga-labeled prostate-specific membrane antigen (PSMA)-11 PET on the intended management of patients with biochemically recurrent prostate cancer. Pre- and postimaging surveys were filled out by the referring providers for patients with biochemical recurrence who were imaged using Ga-PSMA-11 PET. The inclusion criterion for this study was a prostate-specific antigen (PSA) doubling time of less than 12 mo after initial treatment (NCT02611882). Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 25 publications
9
115
1
Order By: Relevance
“…After reviewing the full texts, four articles were excluded from the quantitative analysis (meta‐analysis) due to insufficient data to reassess the correlation between PSA kinetics and DR of PSMA‐PET and 8 studies including about 1,400 patients were finally selected for the meta‐analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full texts, four articles were excluded from the quantitative analysis (meta‐analysis) due to insufficient data to reassess the correlation between PSA kinetics and DR of PSMA‐PET and 8 studies including about 1,400 patients were finally selected for the meta‐analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we demonstrated that up to 29% of men in this patient cohort have disease outside the prostate fossa at the time of imaging with PSMA PET/CT (5). We know that there is a high management impact with PSMA PET/CT in this patient population (7)(8)(9)12,13). However, what Data in parentheses are percentages unless otherwise noted.…”
Section: Discussionmentioning
confidence: 96%
“…Recent publications have reported PSMA PET/CT identifying disease outside the prostate fossa in 28%-43% of men with a rising PSA after RP (5-7). These findings have led to significant changes in patient care, with many patients confirmed with metastatic disease on PSMA PET scans not proceeding to salvage fossa radiotherapy (8,9).…”
mentioning
confidence: 99%
“…In other subgroups, they reported a DR of 93.0% for PSA values between 1 and 2 ng/mL, 72.7% for PSA values between 0.5 and 1 ng/mL, and 57.9% for PSA values between 0.2 and 0.5 ng/mL. Other authors substantially confirmed the same results, which represents the base for an increasing application of PSMA in the clinical routine …”
Section: Evidence Acquisitionmentioning
confidence: 99%